Alcalóides de Aspidosperma auriculatum Standl - BARBOSA, Wagner Luiz Ramos (2011)
Species from genus Aspidosperma show the presence of indol alkaloids. From Aspidosperma quebracho-blanco Schlecht quebracacidine was obtained1, from A. olivaceum. Schmutz and Hunziker2 isolated olivacine, among others substances. This work reports the determination of the chromatographic profile of alkaloid fractions from Aspidosperma auriculatum, by Thin Layer Chromatography and High Performance Liquid Chromatography. At the Brazilian state Pará this plant species has the vernacular name carapanaúba and is traditionally indicated to heal fever and others affections and also malaria. The plant material - stem bark - was extracted with hydrochloridric acid 5%. Three principal alkaloid fractions were extracted at pH 7, pH 8 and pH 11, which were analysed in suitable systems showing characteristic profiles